1959
DOI: 10.1084/jem.109.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Localization of Type 4 Adenovirus

Abstract: Electron microscopic studies by several investigators (1-3) have shown virus-like particles in the nuclei of HeLa cells infected with adenoviruses. Morgan and his associates (3) showed disruption of the nuclear membrane in a few cells with release of virus-like particles into the cytoplasm, but did not note viral development in the cytoplasm. A tremendous number of particles have been observed by electron microscopic examination of thin sections of infected HeLa cells, a finding which seems to be out of propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1959
1959
1966
1966

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Possibilities which can not be excluded on the basis of available data include aggregation of virus so that one infectious unit represents many infectious particles, incomplete separation of infectious virus from cell components, inactivation of infectious virus coincidental with its release from the cell, and the inadequacy of the techniques employed to determine accurately the number of infectious particles. The data of the cellular fractionation studies (7) suggest that the first possibility, namely aggregation, is the most likely explanation for the discrepancy described.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Possibilities which can not be excluded on the basis of available data include aggregation of virus so that one infectious unit represents many infectious particles, incomplete separation of infectious virus from cell components, inactivation of infectious virus coincidental with its release from the cell, and the inadequacy of the techniques employed to determine accurately the number of infectious particles. The data of the cellular fractionation studies (7) suggest that the first possibility, namely aggregation, is the most likely explanation for the discrepancy described.…”
Section: Discussionmentioning
confidence: 81%
“…Such a conclusion is of course justified only if the arrays of virus-like particles found in infected cells are actually aggregates of virus. As discussed in the preceding paper, the results of HeLa cell fractionation studies indicated that infectious type 4 adenovirus was associated with the "cytoplasmic" rather than the "nuclear" fraction, a finding which raised some question about the interpretation of the intranuclear changes (7). When the results of the fractionation studies were obtained, several possibilities concerning the nature of the intranuclear changes were considered.…”
mentioning
confidence: 94%
“…(Heceived December 13, 1964) The use of the fluorescent antibody method of Coons and Kaplan (1) in the past few years added much to our knowledge of the intracellular localization and replication of ~ number of viruses, such as adeno (2,3), reo (4,5), influenza (6), v~ccinia (7,8), psittacosis (9), measles (10) and others (11,12). Among enteroviruses, the most extensively investigated in this respect was poliovirus (13,14,15,16,17).…”
Section: With 13 Figuresmentioning
confidence: 99%